2017
DOI: 10.1073/pnas.1617923114
|View full text |Cite
|
Sign up to set email alerts
|

Self-affirmation facilitates minority middle schoolers' progress along college trajectories

Abstract: Small but timely experiences can have long-term benefits when their psychological effects interact with institutional processes. In a follow-up of two randomized field experiments, a brief values affirmation intervention designed to buffer minority middle schoolers against the threat of negative stereotypes had long-term benefits on college-relevant outcomes. In study 1, conducted in the Mountain West, the intervention increased Latino Americans’ probability of entering a college readiness track rather than a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
102
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 33 publications
5
102
3
Order By: Relevance
“…Follow‐up studies have found that positive effects of self‐affirmation on ethnic minority students persist over time. Remarkably, one study found benefits to college enrolment up to 9 years after the self‐affirmation intervention (Goyer et al ., ) and another found improvements in academic achievement up to 3 years after the intervention, including spanning the transition from middle to high school (Borman, Grigg, Rozek, Hanselman, & Dewey, ). The authors argue that this occurs when the short‐term benefits trigger a set of complex and interconnected processes that recursively build on themselves over long periods.…”
Section: Introductionmentioning
confidence: 99%
“…Follow‐up studies have found that positive effects of self‐affirmation on ethnic minority students persist over time. Remarkably, one study found benefits to college enrolment up to 9 years after the self‐affirmation intervention (Goyer et al ., ) and another found improvements in academic achievement up to 3 years after the intervention, including spanning the transition from middle to high school (Borman, Grigg, Rozek, Hanselman, & Dewey, ). The authors argue that this occurs when the short‐term benefits trigger a set of complex and interconnected processes that recursively build on themselves over long periods.…”
Section: Introductionmentioning
confidence: 99%
“…Although some policies and programs aimed at narrowing these gaps among children and adolescents have shown short-term benefits, these initial successes typically fade away over time (3). Why are these inequalities in our schools so persistent and seemingly intractable, and how did Goyer et al (4) find success when so many others have failed?…”
mentioning
confidence: 99%
“…In PNAS, Goyer et al (4) demonstrate that over time, initial reductions of ∼40% of the academic performance gaps that were realized at the end of the eighth grade, 2 y following the advent of a stereotype threat-buffering, values-affirmation intervention, later helped minority students achieve academic opportunities and outcomes that placed them on a trajectory to a college education. How did the delivery of several affirming 15-min writing activities in the seventh grade fundamentally change the academic outcomes and life chances of these students?…”
mentioning
confidence: 99%
“…diet (Epton et al, 2015), and educational outcomes such as college enrollment over a period of years (e.g., Goyer et al, 2017).…”
Section: Future Directions: Using Self-affirmation In the Context Omentioning
confidence: 99%